Model Gangguan Fungsi Paru pada Petugas Penyapu Jalan di Kota Palembang - Sunarsih, Elvi; Gernauli Purba, Imelda; Trisnaini, Inoy; Minarti, Minarti; Aulia Armawan, Ladyka Viola (Seminar Nasional Lahan Suboptimal, 2024)
Sunarsih, E., Purba, I. G., Trisnaini, I., Minarti, M., & Armawan, V. A. A. (2024). Model of lung function disorders in officers street sweeper in Palembang City. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembangg 21 Oktober 2024. (pp. 906–917).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Air is a mixture of various gases whose ratios vary depending on temperature and air pressure. Exposure to dust in the work environment can lead to different types of lung diseases, resulting in impaired lung function and disability. This study aimed to analyze lung function disorders among highway sweepers in Palembang City. It is a quantitative analytical study using a cross-sectional design. The population for this study includes all highway sweepers, with a sample of 91 out of a total of 95 individuals. The results indicate a relationship between smoking habits, years of work, length of exposure, and disease history with lung function impairment. Among these, length of exposure is the most dominant factor affecting lung function impairment. Age, gender, PM10 levels, TSP levels, nutritional status, and PPE use were not significantly related to lung function disorders. Recommendations include providing appropriate PPE to street sweepers and offering nutritious food to address potential nutritional deficiencies among this group.